A Comprehensive and Comparative Analysis of the Fucoidan Compositional Data Across the Phaeophyceae - Ponce, Nora M. A.; Stortz, Carlos A. (Frontiers in Plant Science, 2020)
In the current review, compositional data on fucoidans extracted from more than hundred different species were surveyed through the available literature. The analysis of crude extracts, purified extracts or carefully isolated fractions is included in tabular form, discriminating the seaweed source by its taxonomical order (and sometimes the family). This survey was able to encounter some similarities between the different species, as well as some differences. Fractions which were obtained through anion-exchange chromatography or cationic detergent precipitation showed the best separation patterns: the fractions with low charge correspond mostly to highly heterogeneous fucoidans, containing (besides fucose) other monosaccharides like xylose, galactose, mannose, rhamnose, and glucuronic acid, and contain low-sulfate/high uronic acid proportions, whereas those with higher total charge usually contain mainly fucose, accompanied with variable proportions of galactose, are highly sulfated and show almost no uronic acids. The latter fractions are usually the most biologically active. Fractions containing intermediate proportions of both polysaccharides appear at middle ionic strengths. This pattern is common for all the orders of brown seaweeds, and most differences appear from the seaweed source (habitat, season), and from the diverse extraction, purification, and analytitcal methods. The Dictyotales appear to be the most atypical order, as usually large proportions of mannose and uronic acids appear, and thus they obscure the differences between the fractions with different charge. Within the family Alariaceae (order Laminariales), the presence of sulfated galactofucans with high galactose content (almost equal to that of fucose) is especially noteworthy.